ANALYSIS OF SOME PHENOL COMPOUNDS AND VITAMINS IN LEAVES OF TURNIP (BRASSICA RAPA L) GROWING IN UZBEKISTAN - I.R. Asqarov; N.B. Atakulova; G.A. Madaminova; S.B.Odilova (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: This article presents a comprehensive study of turnip leaves (Brassica rapa L.) grown in Uzbekistan, focusing on their botanical classification, morphological characteristics, distribution, and chemical composition. Turnip belongs to the Brassicaceae family and is one of the widely cultivated vegetable crops with significant importance in agriculture and the food industry. In common practice, the edible root is mainly utilized, while the leaves remain insufficiently studied despite their potential nutritional value. The research describes the main vegetative organs of the plant, including the root, stem, and leaves, with particular emphasis on the biological and nutritional properties of turnip leaves. The results revealed that turnip leaves are rich in essential macro- and microelements, proteins, vitamins, and biologically active phenolic compounds that are beneficial to human health. The content of macro- and microelements, as well as the quantitative composition of phenolic compounds, was determined using the High-Performance Liquid Chromatography (HPLC) method. Ethanol, acetic acid, and acetonitrile were used as extraction solvents during the analysis. The findings demonstrated that turnip leaves contain significant amounts of phenolic compounds, including flavonoids such as apigenin, which exhibit strong antioxidant activity. Phenolic compounds play a crucial role in protecting the human body from oxidative stress by neutralizing free radicals and reducing the risk of various chronic diseases. Therefore, turnip leaves can be considered a valuable natural source of antioxidants. The obtained results indicate that turnip leaves have high potential for use as functional food ingredients, dietary supplements, and pharmaceutical raw materials.